The geography of friendship - Piper, Sally (University of Queensland Press, 2018)
We can't ever go back, but some journeys require walking the same path again. When three young women set off on a hike through the wilderness they are anticipating the adventure of a lifetime. Over the next five days, as they face up to the challenging terrain, it soon becomes clear they are not alone and the freedom they feel quickly turns to fear. Only when it is too late for them to turn back do they fully appreciate the danger they are in. As their friendship is tested, each girl makes an irrevocable choice; the legacy of which haunts them for years to come. Now in their forties, Samantha, Lisa and Nicole are estranged, but decide to revisit their original hike in an attempt to salvage what they lost. As geography and history collide, they are forced to come to terms with the differences that have grown between them and the true value of friendship.